VD_FINDINFO 18/2013 vom 6. Juni 2013 - VD Tribunal cantonal (2013)
RÉCUSATION, RETRAITVOIE DE DROIT | 6 al. 1 let. a ROTC, 106 al. 1 CPC (CH), 241 CPC (CH), 47 CPC (CH), 50 al. 2 CPC (CH), 8a al. 7 CDPJ